Kikuchi-Fujimoto disease concurrent with aseptic meningitis or encephalitis in children: a case-control study - Bing Liu; Yi Sun; Bing Hu; Wen-yuan Shi; Tian-ming Chen; Lin-lin Liu; Gang Liu (BMC Pediatrics)
Abstract Background This study was performed to summarize the clinical and laboratory features of children with Kikuchi-Fujimoto disease concurrent with aseptic meningitis or encephalitis. Methods A case-control study of children diagnosed with Kikuchi-Fujimoto disease at Beijing Children’s Hospital from January 2015 to December 2023 was conducted to determine the characteristics of the disease when concurrent with aseptic meningitis or encephalitis. Results Our cohort of 64 cases of Kikuchi-Fujimoto disease included 16 children with central nervous system involvement and 48 controls. Among the 16 affected children, the male: female ratio was 1.7:1.0. The age at onset ranged from 3 to 13 years, with a median age of 8 years. All 16 cases had fever, 15 had cervical lymph node tenderness, 11 had headache, and 14 showed decreased white blood cell counts in routine blood tests. Imaging of the head revealed abnormalities in 11 cases, specifically leukoencephalopathy with mostly bilateral involvement. Cervical lymph node tenderness, headache, confusion, convulsions, and elevated C-reactive protein were significantly associated with Kikuchi-Fujimoto disease concurrent with aseptic meningitis or encephalitis (p < 0.05). There was also a significant difference in lactate dehydrogenase levels between children with and without central nervous system involvement (575.8 ± 221.3 vs. 440.0 ± 163.1 U/L, p = 0.014). Conclusions For children with Kikuchi-Fujimoto disease, careful evaluation for central nervous system involvement is warranted when cervical lymph node tenderness, elevated C-reactive protein, or elevated lactate dehydrogenase is present. In children presenting with aseptic meningitis or encephalitis, Kikuchi-Fujimoto disease should be considered as a differential diagnosis. Clinical trial number Not applicable.